Evidence of polar nanoregions in quantum paraelectric KTaO3. (May 2015) - Trybuła, Z.; Miga, S.; Łoś, Sz.; Trybuła, M.; Dec, J.
Abstract: Linear and nonlinear dielectric properties of nominally pure quantum paraelectric potassium tantalate KTaO3 crystals are presented. By use experimental technique to get the higher order electric susceptibility χ 2, and χ 3, in addition to the linear one, χ 1, dielectric loss factor, and the polarization, obtained by integrating the depolarization current measured on zero field heating (ZFH) after field cooling (FC) run, we have proved existence of polar nanoregions (PNR׳s for short) below 40 K in nominally pure potassium tantalate KTaO3 single crystal. Highlights: Linear and nonlinear dielectric properties of KTaO3 crystals are presented. We have proved existence of polar nanoregions in nominally pure KTaO3 single crystal. We propose origin of polarization in nominally pure KTaO3 observed below 40 K.